Michael Attaleiates’ Ἀλβανοὶ and Λατῖνοι: the southern Italian rebels and the changing perception of the Normans in Byzantium - WELTE BERNARDO, Guilherme (Byzantina Symmeikta, 2024)
Michael Attaleiates’ Ἀλβανοὶ and Λατῖνοι: the southern Italian rebels and the changing perception of the Normans in Byzantium This article revises the current interpretation regarding who were the Ἀλβανοὶ (Albans) and Λατῖνοι (Latins) mentioned in Michael Attaleiates’ History, written in the 11th century. While previous scholars identified these groups as Albanians and Normans, the article argues that Attaleiates uses both terms to generically drew a parallel between ancient groups appearing in Greco-Roman historiography and contemporary groups in the southern Italy during his time, like the Lombards. It also suggests that Normans (the "Franks from Italy") are sometimes referred to as Λατῖνοι in the work, particularly due to their association with the Lombard population of southern Italy, where they settled. For a more in-depth analysis, the article identifies two different contexts in which the term Λατῖνοι was used by Attaleiates: the first in association with the Ἀλβανοί (i. e., the Lombards), and the second in parallel with the Φράγγοι (Franks, i.e., the Normans). Through these reexaminations, the article provides new insights into the complex relationships between the medieval Roman Empire and its neighbors in the Italian Peninsula.